An SPX-RLI1 Module Regulates Leaf Inclination in Response to Phosphate Availability in Rice. Issue 4 (2nd April 2018) - Ruan, Wenyuan; Guo, Meina; Xu, Lei; Wang, Xueqing; Zhao, Hongyu; Wang, Junmin; Yi, Keke
Abstract : SPX and RLI1 regulate lamina joint cell expansion, thus increasing leaf inclination in response to Pi deficiency in rice. Abstract: Leaf erectness is one of the key traits of plant architecture; in grains, plants with upright leaves can be planted close together, thus benefiting yield/unit area. Many factors, such as hormones, affect leaf inclination; however, how nutrition status, in particular phosphate (Pi) availability, affects leaf inclination remains largely unexplained. Here, we show that in rice ( Oryza sativa ), Pi deficiency stress inhibits lamina joint cell elongation, thus restricting lamina joint size and inducing leaf erectness in rice. The Pi starvation-induced proteins SPX1 (for Syg1/Pho81/XPR1) and SPX2 play a negative role in the regulation of leaf inclination. We further identified an SPX1-interacting protein, REGULATOR OF LEAF INCLINATION1 (RLI1), which positively regulates leaf inclination by affecting lamina joint cell elongation in rice. The rli1 mutants showed reduced leaf inclination and the RLI1 overexpressors showed increased leaf inclination. RLI1 directly activates the downstream genes BRASSINOSTEROID UPREGULATED1 ( BU1 ) and BU1-LIKE 1 COMPLEX1 to control elongation of the lamina joint cells, therefore enhancing leaf inclination. We also found that Pi deficiency repressed the expression of RLI1 . SPX1 protein interacts directly with RLI1, which could prevent RLI1 binding to the promoters of downstream genes. Therefore, SPX and RLI1 form a module to regulate leaf inclination in response to external Pi availability in rice.